2005
DOI: 10.1007/s11274-005-9028-x
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Butanedione monoxime increases sensitivity to Nikkomycin Z in the budding yeast Saccharomyces cerevisiae

Abstract: Nikkomycin Z (NZ) is a competitive inhibitor of chitin synthase III in the yeast Myosin type II-deficient yeast strains () display a dramatic reduction in growth when chitin synthase III activity is inhibited by NZ, supporting the contention that actomyosin motility plays an important role in maintaining cell wall integrity. A proposed inhibitor of cortical actin polymerization , 2,3-butanedione monoxime (BDM), also inhibits growth of wild-type yeast strains at a concentration of 20 mM. In this study, we assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
12
1
Order By: Relevance
“…We found that a total of 10 synthetic lethal interactions (Breton and Aigle, 1998;Davierwala et al, 2005;Roumanie et al, 2000;Vallen et al, 2000;Wang and Bretscher, 1995) and two synthetic growth interactions (Lillie and Brown, 1998) have been previously described for myo1, while 76 synthetic lethal (Friesen et al, 2006;Goehring et al, 2003;Lesage et al, 2005;Tong et al, 2004) and two synthetic growth interactions (Castrejon et al, 2006;Sobering et al, 2004) have been previously described for chs3. There were no common synthetic lethal or synthetic growth interactions described between myo1 and chs3 in the SGD, although we and others have reported a synthetic growth interaction (Rivera-Molina et al, 2006;Schmidt et al, 2002). Deletions of smi1 or fks1 were found to have synthetic lethal interactions with chs3 and ubc4 (Lesage et al, 2005;Tong et al, 2004).…”
Section: N L Díaz-blanco and J R Rodríguez-medinacontrasting
confidence: 51%
See 1 more Smart Citation
“…We found that a total of 10 synthetic lethal interactions (Breton and Aigle, 1998;Davierwala et al, 2005;Roumanie et al, 2000;Vallen et al, 2000;Wang and Bretscher, 1995) and two synthetic growth interactions (Lillie and Brown, 1998) have been previously described for myo1, while 76 synthetic lethal (Friesen et al, 2006;Goehring et al, 2003;Lesage et al, 2005;Tong et al, 2004) and two synthetic growth interactions (Castrejon et al, 2006;Sobering et al, 2004) have been previously described for chs3. There were no common synthetic lethal or synthetic growth interactions described between myo1 and chs3 in the SGD, although we and others have reported a synthetic growth interaction (Rivera-Molina et al, 2006;Schmidt et al, 2002). Deletions of smi1 or fks1 were found to have synthetic lethal interactions with chs3 and ubc4 (Lesage et al, 2005;Tong et al, 2004).…”
Section: N L Díaz-blanco and J R Rodríguez-medinacontrasting
confidence: 51%
“…Culture media were supplemented with 2% glucose (glu) or 2% galactose (gal) (Sigma) and 1× nitrogen base without amino acids (Difco, Becton Dickinson and Co.) at 25 • C. The proteasome inhibitor clasto-lactacystin β-lactone (Calbiochem) was reconstituted in DMSO and used at a concentration of 10 µM. Nikkomycin Z (Sigma) was used at concentrations previously determined for agar (30 µg/ml) and broth (6.25 µM) media (Rivera-Molina et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The proteasome inhibitor clasto ‐lactacystin β‐lactone (Calbiochem) was reconstituted in DMSO and used at a concentration of 10 µ M . Nikkomycin Z (Sigma) was used at concentrations previously determined for agar (30 µg/ml) and broth (6.25 µ M ) media (Rivera‐Molina et al , 2006).…”
Section: Methodsmentioning
confidence: 99%
“…CSIII (also called Chs3p, for its catalytic subunit) is also required for maintenance of lateral cell wall chitin synthesis and for chitin ring formation at the bud site during G 1 phase (Shaw et al , 1991). Consequently, a deletion of CHS3 causes a synthetic growth defect in most myo1 strains (Schmidt et al , 2002) and hypersensitivity to low doses of nikkomycin Z (NZ), an irreversible competitive inhibitor of CSIII (Rivera‐Molina et al , 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation